Literatur Review: Analisis Usaha Undangan Digital Serta Penggunaan Media Sosial Sebagai Media Promosi - Shelly Ayu Andesty; Dety Mulyanti (Pusat Riset dan Inovasi Nasional, 2023)
In the current era of modernization, many things have begun to use technological developments, including the delivery and dissemination of information. This development is marked by changes in methods in various fields, leaving manual methods and replacing them with the use of modern technology. With the rapid advancement of information technology, it makes it easier for business people to develop creativity and market a product, including the digital invitation business. This type of digital invitation is gaining popularity not only because it is considered easier to distribute, low production costs, and a variety of designs. Digital invitations are visually more attractive because media such as photos, text, animation and audio can be added. This study aims to analyze several articles related to public interest in digital invitation business opportunities. The design used is literature review, articles are collected using search engines such as neti.com, google scholar, and Sciencedirect. With the criteria for articles published in 2019-2021. Based on the articles collected, the results of the analysis show that digital invitations have considerable business potential for business people and make it easier for users to convey information.